Complete Symmetrie functions in several variables and k-Fibonacci numbers - Boussayoud, Ali; Boughaba, Souhila; Araci, Serkan (Utilitas Mathematica, 2020)
We first compute the generating functions by making use of symmetric functions given in this paper. Motivated by the recent works including the products of several special numbers, we are concerned here only with the question of manipulating combinatorial objects, known as symmetric operators. The proposed generalized symmetric functions can be used to find explicit formulas of the k-Fibonacci numbers k-Pell numbers and product of sequences and symmetric function in several variables. © 2020 Utilitas Mathematica Publishing Inc.. All rights reserved.